Spiritual Space or Theme Park? A Case of Postmodern Simulated Experience (KEMANUSIAAN The Asian Journal of Humanities, 2017)
The small village temple Wat Rong Khun on the outskirts of Chiang Rai in northern Thailand is a modern artistic experiment created, at least partly, to attract both international and national tourists. As such, it is very successful – hundreds of tourists come to the temple on a daily basis. Yet, although it is a Buddhist temple, and as such one might expect the tourist to adopt a reverential gaze when visiting it, this essay shows how the tourist’s experience is disconnected from the spiritual and becomes superficial. This disconnect is due in no small part to the highly decorated surfaces of the temple, which are overwhelming, plastic and undeniably strange for a Buddhist temple. The temple is not only highly decorated, but also regulated and restrictive. All visitors are monitored and surveilled to make sure they approach the space and the different buildings as they should, and therefore experience them as intended for maximum visual impact. Visitors therefore approach the temple as they would other simulated postmodern spaces available to tourists. Their experience of the surfaces is reinforced by the commercial aspect of material culture available in the temple gift shop, where other objects of similar artistic and decorative qualities, as opposed to religious paraphernalia, are available for sale. Although the artistic programme of Wat Rong Khun has a lot to offer when it comes to religious teaching and iconography, the temple is here analysed as a postmodern simulated space, a simulacrum reinforced by consumerism, of both the visual (overabundant decorative temple surface) and material culture (artistic prints available in the gift shop).